INVESTMENT IN CONSTRUCTION IN EMERGENCIES - BENEFITS AND RISKS - Nikolić, Ljubica (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
The reasons for declaring a state of emergency in a certain territory can be different, even epidemics of infectious diseases. In extraordinary circumstances, economic entities assess the expected returns and risks and adjust their business decisions to new conditions, while expecting reactions from the Public sector that will enable them to function. In this paper, the effects of the emergency situation, primarily the Covid-19 virus pandemic, on investment in construction will be analyzed. The construction of a building is a complex project even in regular circumstances due to: the complexity of legal relations between several persons, long duration of implementation, numerous administrative and legal obligations of investors and contractors, as well as the value of the project. An emergency situation, depending on the cause and the applied measures, can significantly disrupt and endanger many business relations, including those between the client and the construction contractor. On the other hand, in some emergency situations, the owners of financial capital, in order to preserve the real value of theire assets, among other things, buy construction facilities. Increased demand, and thus the price increase of construction facilities, stimulates investments in construction. In the altered and aggravated business conditions caused by the pandemic, construction projects, at the same time, become challenging, risky and profitable.